2014
DOI: 10.1371/journal.pone.0096676
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Risk Factors for Delirium in Living Donor Liver Transplantation Patients in Intensive Care Units

Abstract: BackgroundDelirium is one of the main causes of increased length of intensive care unit (ICU) stay among patients who have undergone living donor liver transplantation (LDLT). We aimed to evaluate risk factors for delirium after LDLT as well as to investigate whether delirium impacts the length of ICU and hospital stay.MethodsSeventy-eight patients who underwent LDLT during the period January 2010 to December 2012 at a single medical center were enrolled. The Confusion Assessment Method for the Intensive Care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 22 publications
10
47
4
Order By: Relevance
“…The total incidence of delirium was 37% in the present study. This incidence is generally consistent with the incidences reported in previous studies [ 22 , 24 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The total incidence of delirium was 37% in the present study. This incidence is generally consistent with the incidences reported in previous studies [ 22 , 24 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…To test this hypothesis, further basic and clinical research is 101 necessary. A low serum Na level has also been associated with the incidence of delirium in a few reports [22][23][24] . In this study, the serum Na levels on POD 3 were significantly lower in the high-risk group compared to the low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that pathogenesis of POD presenting after LT is multifactorial: infections, organ failure, encephalopathy and neurotoxicity of immunosuppressants have all been called into question. Reported POD incidence in LT patients ranges from 10 to 47% [10][11][12][13][14][15][16]. Also in the setting of LT, POD has been associated with prolonged hospital and ICU stay, and increased mortality.…”
Section: Introductionmentioning
confidence: 99%